UNDERSTANDING LEARNING DIFFICULTY ISSUES BASED ON PSYCHOLOGY IN PRIMARY SCHOOL AGE STUDENTS - Rohma, Wulidatul; Mu’alimin, Mu’alimin; Usriyah, Lailatul; Sutomo, Moh (Program Studi PGMI, 2024)
Learning difficulties are a problem that can arise anywhere and can be experienced by any-one. Learning difficulties are not always caused by low intelligence, but can also be caused by non-intelligence factors. Parenting has a role in children's development, including their personality and also in their learning process. This research was conducted to find out the causes of learning difficulties experienced by school-age children. The method used is qual-itative research, with an explanatory case study. The subject in this study is a 10-year- old school-age child. The data collected in this research is by using interview, observation, intel-ligence test (CFIT test), and graphic test. The results showed that the learning difficulties experienced by the subject were not only caused by intelligence factors, but also influenced by the parenting received by the subject in the family. The subject has an intelligence level below average, which puts him in the category of slow learners. In addition, permissive par-enting and excessive attention from family members, especially the grandmother, also con-tributed to the subject's learning difficulties.